2007
DOI: 10.2139/ssrn.1075204
|View full text |Cite
|
Sign up to set email alerts
|

Firm Productivity Dynamics in Spain

Abstract: We have constructed a new database aimed at the study of the relation between firm demography and labour productivity, with a large number of Spanish firms from both industry and service sectors. This database allows us to analyze in detail the degree of dispersion and persistence of productivity levels, as well as the contribution of firm demography to productivity growth. This analysis has been done at different levels of sector aggregation. We have also studied explicitly the differential role of small and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(6 citation statements)
references
References 44 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…() Both size and age effects differ across industries and firms (Hannan et al. ; López‐García, Puente, and Gómez ).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…() Both size and age effects differ across industries and firms (Hannan et al. ; López‐García, Puente, and Gómez ).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…As pointed out in Thompson (2005), theories that could explain the observed pattern include learning, financial frictions, and the fact that older firms are possibly active in a larger number of submarkets. A few studies find an inverted U-shaped relationship between firm age and firm exit Both size and age effects differ across industries and firms (Hannan et al 1998;López-García, Puente, and Gómez 2007).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…20 Figure 4 compares the evolution of the average TFP growth at the firm level (left hand side panel), with that at the aggregate level (right panel). 21 We can see that the growth rate of the average firm TFP has been continuously negative and decreasing since the beginning of the crisis (between 2010 and 2012 there is a slight increase in the growth rate, though it remains below -5%). For aggregate TFP, the growth rate is negative but closer to zero during the crisis period.…”
Section: Evolution Of the Estimated Tfpmentioning
confidence: 92%
“…For the specific case of Spain, López-García et al (2007) found that the contribution of large firms to productivity growth is more important than the contribution of small businesses if only incumbent firms are taken into account. López-García and Sánchez (2010) show, moreover, that Spanish micro-enterprises are less productive than European micro-enterprises in all sectors.…”
mentioning
confidence: 99%